AGE-RELATED CHARACTERISTICS OF THE MACROSTRUCTURE, LIPID COMPOSITION, STRENGTH AND GROWTH OF SHEEP WOOL - Tkachuk , В.; Ohorodnyk , Н.; Motko , Н.; Pavkovych , C.; Dudar , І.; Pashchak , М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The results of experimental studies of the age-related characteristics of the macrostructure, lipid composition, strength and growth of sheep wool are presented. The study was conducted on ewe lambs and ewes of the Prekos breed. As a result of the conducted research, it was established that the wool of ewe lambs, in comparison with ewes, contains probably a larger amount of alpha-keratosis (Р < 0.05), i.e. protein macro- and microfibrils, and a smaller amount of gamma-keratosis (Р < 0.05), that is, the wool fiber matrix. Significant changes in the lipid composition of wool fibers are observed against the background of almost the same content of total internal lipids – 0.97 % in ewe lambs and 1.03 % in ewes. In particular, the wool of full-aged ewes, in comparison with ewe lambs, is characterized by probably a higher content of non-esterified fatty acids (Р < 0.01) and a lower content of esterified cholesterol (Р < 0.05). Such results also indicate that, with age, processes of hydrolysis, oxidation, and saponification of their lipid components occur in wool fibers. It was also shown that ewe lamb wool contains a lower amount of sulfolipids (Р < 0.05) and a higher amount of ceramides (Р < 0.05). As is known, the latter is important in shaping the surface properties of hair, influencing its hydrophobic properties, diffusion and sorption, resistance to weather conditions and degradation processes, as well as its physical properties, particularly strength. Differences in the macrostructure and lipid composition of wool of different age groups of sheep were also reflected in the physical properties of the fibers, in particular their strength. Thus, the wool of ewe lambs, although unlikely, was stronger, compared to the wool of ewes. As for wool growth, no significant age differences were found under the conditions of our research.